2014
DOI: 10.1021/am506464f
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Synthesis and Assembly of Silver Nanoparticles to Three-Demensional Superstructures for Sensitive Surface-Enhanced Raman Spectroscopy Detection

Abstract: Construction of superstructures with controllable morphologies from NPs is of great scientific and technological importance. A one-step method for simultaneous synthesis and assembly of Ag NPs to three-dimensional (3D) nanoporous superstructures is demonstrated. By varying the adsorption time of Ag precursors, an array of well-defined Ag superstructures with different morphologies are harvested. A "hot spot"-rich substrate for surface-enhanced Raman spectroscopy is established, which exhibits high sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 43 publications
(90 reference statements)
0
24
0
Order By: Relevance
“…were fabricated and tested as versatile SERS substrates [12][13][14][15][16][17][18][19][20][21][22][23] . Specifically, porous materials, nanostructures and nanoparticles, routinely reaching uniform SERS enhancement sufficient to overcome single-molecule detection limit independently on excitation/detection conditions, are of growing interest [24][25][26] .…”
mentioning
confidence: 99%
“…were fabricated and tested as versatile SERS substrates [12][13][14][15][16][17][18][19][20][21][22][23] . Specifically, porous materials, nanostructures and nanoparticles, routinely reaching uniform SERS enhancement sufficient to overcome single-molecule detection limit independently on excitation/detection conditions, are of growing interest [24][25][26] .…”
mentioning
confidence: 99%
“…From the scanning‐electron microscopy (SEM) images, we observe that mostly trigonal supracrystals have been built up (Figure a–c). These structures have already been presented in numerous publications . By SAXS, HRSEM, and TEM measurements, we can confirm that these supracrystals are built up from an assembly of the NPs into fcc superlattices with lattice parameters of about 10.4 nm.…”
Section: Resultsmentioning
confidence: 85%
“…[13] Besides these merits, it has been demonstrated that polymer brushes can act as capping agents to control the growth of noble-metalp articles. [14] Although,in our previousr eports,h ierarchical noble-metal particles could be obtained on the surfaceo ft he polymer brushesgrafted-GO films, the noble-metal structures are highly dependent on the choice of the external reducinga gent. [15,16] To date,c ontrolled growth of 3D noble-metalp articles by as pontaneous redox reactionb etween graphene with grafted polymer brushes and metal salts withoutt he use of any additional reducing agent has rarely been reported.…”
Section: Introductionmentioning
confidence: 86%